On the operational management of intensive care unit´s long term stays amid Covid-19 / Sobre a gestão operacional das estadias de longo prazo da unidade de cuidados intensivos em entre Covid-19 - Prado, Lorena Teixeira Rodrigues Pinheiro do (2020)
This paper analyzes the management situation, or its lack, in view of the problem of extrapolating hospitalizations to a long-term bed situation. For this understanding, we sought from the literature on hospital management the concepts for understanding its foundation and the typical problems faced in hospitals. It is concluded that the adequate training of the team in hospital management and in the adoption of the respective management recommendations constitute priority measures must be a priority so that the hospital administration can use predictive techniques in resource management of Intensive Care Unit during the pandemic that causes COVID- 19.